Learning to Teach and Professional Identity: Images of Personal and Professional Recognition - J. Alberto Fajardo Castañeda (Universidad Nacional de Colombia, 2014)
This study aims to investigate how pre-service teachers construct their professional identities from the interplay between participation in a teacher community and their systems of knowledge and beliefs. A group of six Colombian pre-service teachers in the final stage of their five-year teacher education programme were the research participants. Interviews, stimulated recall, and on-line blogs as methods of data collection, and content and conversation analyses as the analytical approaches, were used. The findings reveal that while the process of learning to teach is individually constructed and experienced, it is socially negotiated.